Epigallocatechin-3-gallate at the nanoscale: a new strategy for cancer treatment - Wenxue Sun; Yizhuang Yang; Cuiyun Wang; Mengmeng Liu; Jianhua Wang; Sen Qiao; Pei Jiang; Changgang Sun; Shulong Jiang (Taylor & Francis Group, 2024)
Context Epigallocatechin-3-gallate (EGCG), the predominant catechin in green tea, has shown the potential to combat various types of cancer cells through its ability to modulate multiple signaling pathways. However, its low bioavailability and rapid degradation hinder its clinical application.Objective This review explores the potential of nanoencapsulation to enhance the stability, bioavailability, and therapeutic efficacy of EGCG in cancer treatment.Methods We searched the PubMed database from 2019 to the present, using 'epigallocatechin gallate', 'EGCG', and 'nanoparticles' as search terms to identify pertinent literature. This review examines recent nano-engineering technology advancements that encapsulate EGCG within various nanocarriers. The focus was on evaluating the types of nanoparticles used, their synthesis methods, and the technologies applied to optimize drug delivery, diagnostic capabilities, and therapeutic outcomes.Results Nanoparticles improve the physicochemical stability and pharmacokinetics of EGCG, leading to enhanced therapeutic outcomes in cancer treatment. Nanoencapsulation allows for targeted drug delivery, controlled release, enhanced cellular uptake, and reduced premature degradation of EGCG. The studies highlighted include those where EGCG-loaded nanoparticles significantly inhibited tumor growth in various models, demonstrating enhanced penetration and efficacy through active targeting mechanisms.Conclusions Nanoencapsulation of EGCG represents a promising approach in oncology, offering multiple therapeutic benefits over its unencapsulated form. Although the results so far are promising, further research is necessary to fully optimize the design of these nanosystems to ensure their safety, efficacy, and clinical viability.